Twenty‐year follow‐up of the facial phenotype of Brazilian patients with Sotos syndrome. Issue 12 (18th August 2021) - Castro, Matheus Augusto Araújo; dos Santos, Juliana Heather Vedovato; Honjo, Rachel Sayuri; Yamamoto, Guilherme Lopes; Bertola, Débora Romeo; Hurst, Anna C.; Chorich, Lynn P.; Layman, Lawrence C.; Kim, Chong Ae; Kim, Hyung‐Goo
Abstract: Sotos syndrome is characterized by overgrowth starting before birth through childhood with intellectual disability and craniofacial anomalies. The majority of patients are large for gestational age with developmental delay or intellectual disability. The majority of cases are caused by pathogenic variants in NSD1 . The most consistent physical features in this disorder are facial dysmorphisms including prominent forehead, downslanted palpebral fissures, prognathism with a pointed chin, and a long and narrow face. We present a follow‐up to a cohort of 11 individuals found to harbor heterozygous, pathogenic, or likely pathogenic variants in NSD1 . We analyzed the facial dysmorphisms and the condition using retrospective over 20 years. Among these patients, followed in our medical genetics outpatient clinic for variable periods of time, all had a phenotype compatible with the characteristic Sotos syndrome facial features, which evolved with time and became superimposed with natural aging modifications. We present here a long‐term follow‐up of facial features of Brazilian patients with molecularly confirmed Sotos syndrome. In this largest Brazilian cohort of molecularly confirmed patients with Sotos syndrome to date, we provide a careful description of the facial phenotype, which becomes less pronounced with aging and possibly more difficult to recognize in adults. These results may have broad clinical implications for diagnosis and add to the global clinical delineation of this condition.